Literary Canon and Political Correctness. Perspectives of a conflict - Eder, Jürgen (Transfer. Reception Studies, 2022)
The discussion about aspects of political-moral correctness in the present is becoming ever sharper, more all-encompassing. It has also affected literature for a long time, and while at the present stage of the debate it is primarily works of contemporary literature that are affected, it is foreseeable and in part already evident that the discussion will not stop there. Using the work of Heinrich von Kleist as an example, we will show the way in which even canonical texts and authors are threatened by questions about their correctness and to what extent this can endanger aesthetic freedom as a whole.